PEMAHAMAN KONSEP MATEMATIS MELALUI MODEL WEE DENGAN STRATEGI QSH DITINJAU DARI SELF REGULATION - Tri Wahyuni; Komarudin Komarudin; Bambang Sri Anggoro (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The purpose of this research were to find out the difference in effectiveness between WEE model with QSH strategy and conventional learning, the difference between high, medium and low Self Regulation, and the interaction between learning model and Self Regulation towards the student’s ability of understanding mathematical concept. This research was Quasy Experiment, population were all of Class X Science SMAN 14 Bandar Lampung academic year 2018/2019. The sample class used were two classes by using technique Cluster Random Sampling. Hypothesis testing using two-way ANOVA with . The results of this research were: (1)WEE model with QSH strategy more effective than conventional model learning towards the student’s ability of understanding mathematical concept. (2)The ability to understand mathematical concept with high Self Regulation is better than medium and low Self Regulation, whereas there was no difference between medium and low Self Regulation. (3)There was no interaction between learning model and Self Regulation towards the student’s ability of understanding mathematical concept.